2019
DOI: 10.1186/s13020-019-0279-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human carboxylesterases by ginsenosides: structure–activity relationships and inhibitory mechanism

Abstract: BackgroundHuman carboxylesterases (hCES) are key serine hydrolases responsible for the hydrolysis of a wide range of endogenous and xenobiotic esters. Although it has been reported that some ginsenosides can modulate the activities of various enzymes, the inhibitory effects of ginsenosides on hCES have not been well-investigated.MethodsIn this study, more than 20 ginsenosides were collected and their inhibitory effects on hCES1A and hCES2A were assayed using the highly specific fluorescent probe substrates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Carboxylesterases surpass the activity of arylesterase, and betamethasone 17-valerate is a substrate of carboxylesterases ( Bätz et al, 2013 ). Protopanaxadiol(PPD) ginsenosides exhibited strong inhibition on carboxylesterases ( Sun et al, 2019 ). These enzymes and microbiome could probably be involved in the biotransformation of applied ginsenosides in 3-D human tissue model.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxylesterases surpass the activity of arylesterase, and betamethasone 17-valerate is a substrate of carboxylesterases ( Bätz et al, 2013 ). Protopanaxadiol(PPD) ginsenosides exhibited strong inhibition on carboxylesterases ( Sun et al, 2019 ). These enzymes and microbiome could probably be involved in the biotransformation of applied ginsenosides in 3-D human tissue model.…”
Section: Discussionmentioning
confidence: 99%
“…However, an influence on the half-life of drugs of abuse may also be expected. Furthermore, previous studies showed that several natural products such as cannabis or ginsenosides have an impact on hCES1 activity (Qian et al 2020;Sun et al 2019). For instance, the three major cannabinoids of Cannabis sativa, tetrahydrocannabinol, cannabidiol, and cannabinol, were shown to reduce the hepatic hydrolysis of heroin, which is a substrate of the hCES1 subfamily (Meyer et al 2015;Qian et al 2020).…”
Section: Enzyme Kinetic Studiesmentioning
confidence: 99%
“…In addition, drug-drug interaction (DDI) is significant safety concerns in clinical medication [17][18][19]. Inhibition or induction of human CYP or UGT isozymes could potentially adverse clinical DDI and result in metabolic disorders for endogenous components [20][21][22].…”
Section: Introductionmentioning
confidence: 99%